2019
DOI: 10.1002/ese3.482
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the overburden movement and stress evolution in multi‐seam mining with residual pillars

Abstract: When faced with multi‐seam mining, some coal pillars are left to support the overlying strata when mining the lower seam, where stress concentration usually occurs. When the working face in the lower seam advances to the area influenced by these coal pillars, high ground pressure behavior occurs. Furthermore, the instability of coal pillars under the participation of the roof may induce rock burst, which threaten the safe production of coal mine. To study the roof strata movement and coal pillar instability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Tassew et al [ 6 ] studied the mechanical properties of glass fiber reinforced ceramic concrete through laboratory tests, and the results showed that it had good workability and mechanical properties. Shi et al [ 7 , 8 , 9 , 10 , 11 ] through mechanical experimental research, revealed the effect of ARGF as an admixing material on the performance of concrete grouting materials, and it has been used in coal mines. Nourredine [ 12 ] studied the effects of curing conditions on the durability of cement-based ARGFs using SEM and XRD techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Tassew et al [ 6 ] studied the mechanical properties of glass fiber reinforced ceramic concrete through laboratory tests, and the results showed that it had good workability and mechanical properties. Shi et al [ 7 , 8 , 9 , 10 , 11 ] through mechanical experimental research, revealed the effect of ARGF as an admixing material on the performance of concrete grouting materials, and it has been used in coal mines. Nourredine [ 12 ] studied the effects of curing conditions on the durability of cement-based ARGFs using SEM and XRD techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Ghabraie et al [28] simulated the law of overburden collapse in multiseam coal pillar mining by means of laboratory physical simulation technology. Tian et al [29] and Huang and Cao [30] also used physical simulation technology to study the roof strata movement and coal pillar instability in the process of multiseam mining. Sun et al [31] studied the stability of the overlying remaining coal pillars by using the elastic-plastic theory and the slip line field theory.…”
Section: Introductionmentioning
confidence: 99%
“…Sivakugan et al [3] summarized two methods to solve the stress and analyzed the stress difference through a variety of research methods. Tian et al [4] discovered that the abutment pressure of coal pillars doubled, the roof damage intensified, and the scope of overburden structure failure increased under the condition of multiseam mining. Chai et al [5] carried out a research on the internal relationship between overburden structure and surface deformation in the mining process, controlled by the key strata of ultrathick conglomerate which was divided into three stages.…”
Section: Introductionmentioning
confidence: 99%